Etiology of Drug Addiction Sociology (Drug Control Headquarters, Research and Education Office, 2004)
The phenomenon of illicit drugs is a physical fact with clear characteristics and objective effects which are measurable. However, its effects may or may not be compatible with observer's mental concept. One of the accepted definitions of illicit drugs in social sciences is that they affect on individuals' psycho conditions namely the function of brain, spirit, kindness, feelings, understandings and thinking processes in different ways. The present study shows that only the real effects of illicit drugs do not determine their effects on consumers rather individual's motivation to drug consumption, social environment, social orders and drug consumption methods affect on the consequences of such drugs. In the meantime, hidden social motivations behind drug use and emphasizing on treatment methods are among important factors in drug addiction prevention.